Long-term monitoring of metal pollution by urban trees - Gratani, Loretta; Crescente, Maria Fiore; Varone, Laura (Atmospheric Environment, 2008)
The atmospheric pollution level in Rome was monitored in the year 2006. Five sites in the historical centre were considered. The concentration of Al, Fe, Cu, Zn, and Pb was analysed in washed and unwashed Quercus ilex leaf samples. Moreover, in order to verify the changes in atmospheric pollution in the historical centre of the city after the introduction of the limited trafﬁc zone (LTZ), previous data collected in the years 1979 and 1996 were also considered. The leaf’s internal concentration of Al, Fe, Cu, Zn, and Pb was 28, 22, 40, 77 and 37%, respectively, of the total concentration, and it was in the same range monitored in the years 1979 and 1996. The results underlined a signiﬁcant (p < 0.05) decreasing of metal concentration on unwashed leaves with on an average 92%, compared to ones monitored in the year 1979. The mean value of the total trafﬁc ﬂow during the limitated period (Monday to Friday, from 6:30 a.m. to 6:00 p.m, and Saturday from 2:00 to 6:00 p.m.) was 75.000 vehicles, compared to 90.000 ones before the electronic gates were activated; moreover, a 15% decrease in the daily trafﬁc peak (8:30–9:30 a.m) was monitored. The metal concentration in Q. ilex leaves was be related to motor vehicle emissions, conﬁrmed also by PCA. The data obtained on the leaf metal concentration trend in Rome, over a period of 27 years, underlined the importance of the City Council provisions. These results conﬁrmed the use of Q. ilex for long-term monitoring of metal concentration in those urban areas where the species was naturally present, and widely distributed in the landscape.
Keywords: Bio-monitor; Metal pollution; Quercus ilex; rome; Vehicular trafﬁc

Carbon sequestration by Quercus ilex L. and Quercus pubescens Willd. and their contribution to decreasing air temperature in Rome - Gratani, Loretta; Varone, Laura (Urban Ecosystems, 2006)
Carbon sequestration capability by Quercus ilex L and Quercus pubescens Willd., widely distributed in the city of Rome, and their contribution to decreasing air temperature were investigated. Crown volume is the most signiﬁcant (p < 0.01) variable explaining variation of air temperature below the tree crown. Q. pubescens gives a higher contribution to decreasing air temperature during the hottest months, due to its inherent larger crown volume than Q. ilex (252 ± 19 and 533 ± 52 m3 , respectively for the large size). Moreover, our results show the existence of a strong urban carbon dioxide dome with a peak CO2 concentration (on an average 432 ± 37 ppm) at polluted sites, 16% greater than at control sites. Total carbon sequestration is 84 ± 12 and 111 ± 9 Kg year−1 of CO2 for the small Q. ilex and Q. pubescens tree size,respectively, and 151 ± 10 and 185 ± 7 Kg year−1 of CO2 for the large Q. ilex and Q. pubescen tree size, respectively. Q. pubescens, by its higher total photosynthetic leaf surface area (39% higher than Q. ilex) and its higher mean yearly photosynthetic rates (48% higher than Q. ilex) seems to have a greater role than Q. ilex. However, taking into account the leaf longevity (i.e. 12 ± 3 months for Q. ilex and 4 ± 2 months for Q. pubescens), the evergreen species, by its continuous photosynthetic activity, contributes to reduce CO2 throughout the year, and in particular during the winter months, when trafﬁc volume has a pick, than Q. pubescens.
Keywords: Carbon Sequestration; evergreen and Deciduous species; heat island; lai; tree structure